Relationship of ENSO (El Nio Southernoscillation ) and monsoon index on variability of rainfall and sea surface height in coastal City Semarang, Central Java - Rosyidah Rosyidah; Kunarso Kunarso; Elis Indrayanti (Depik, 2022)
The city of Semarang is one of the coastal areas in Indonesia that is prone to flooding. Flood events that often occur in the Semarang City area can be triggered by high rainfall. Variations in rainfall and sea level are closely related to global atmospheric circulation such as ENSO and regional atmospheric circulation, Monsoon. This study aims to examine the relationship between ENSO and Monsoon with the distribution of rainfall and sea level in coastal city Semarang from 2012 to 2021. Correlation and composite analysis were used to analyze the relationship and impact of ENSO and Monsoon phenomena on rainfall and sea level. The results showed the strong correlation of the ENSO index (Southern Oscillation Index) to rainfall in the JJA and SON periods. Generally, El Nio (La Nia) has an impact on increasing (decreasing) rainfall. Meanwhile, Australian Summer Monsoon Index (AUSMI) only strongly correlates with rainfall in the SON period. The westerly (eastern) wind indicated by a positive (negative) monsoon index in the SON period has the effect of increasing (reducing) rainfall. The ENSO phenomenon with sea level during the JJA period has a strong relationship. In JJA, the highest sea level (maximum tide) rises by 12.6 cm during El Nio and decreases by 0.6 cm during La Nia. Meanwhile, the lowest sea level (minimum low tide) decreased by 16.6 cm during El Nio and increased by 0.7 cm during La Nia. These results can explain the influence of global and regional atmospheric circulation on a local scale on the coast of Semarang City.Keywords:RainfallSea levelEl NioLa NiaMonsoon